Minimally Invasive Destructive, Ablative, and Disconnective Epilepsy Surgery - Treiber, Jeffrey M.; Bayley, James C.; Curry, Daniel (Journal of Pediatric Epilepsy, 2023)
Conventional epilepsy surgery performed by microsurgical dissection typically requires large cranial working windows created with high-speed drills and lengthy incisions. In the past few decades, minimally invasive techniques have been developed with smaller incisions, comparable efficacy, shorter hospitalizations, and better safety profiles. These minimally invasive alternatives utilize stereotactic, ultrasonic, radiotherapeutic, and endoscopic techniques. Although not able to completely replace conventional surgery for all etiologies of epilepsy, these minimally invasive techniques have revolutionized modern epilepsy surgery and have been an invaluable asset to the neurosurgeon's repertoire. The endoscope has allowed for surgeons to have adequate visualization during resective and disconnective epilepsy surgeries using keyhole or miniature craniotomies. Modern stereotactic techniques such as laser interstitial thermal therapy and radiofrequency ablation can be used as viable alternatives for mesial temporal lobe epilepsy and can destroy lesional tissue deep areas without the approach-related morbidity of microsurgery such as with hypothalamic hamartomas. These stereotactic techniques do not preclude future surgery in the settings of treatment failure and have been used successfully after failed conventional surgery. Multiple ablation corridors can be performed in a single procedure that can be used for lesioning of large targets or to simplify treating multifocal epilepsies. These stereotactic techniques have even been used successfully to perform disconnective procedures such as hemispherotomies and corpus callosotomies. In patients unable to tolerate surgery, stereotactic radiosurgery is a minimally invasive option that can result in improved seizure control with minimal procedural risks. Advances in minimally invasive neurosurgery provide viable treatment options for drug-resistant epilepsy with quicker recovery, less injury to functional brain, and for patients that may otherwise not choose conventional surgery.
Keywords: pediatric epilepsy; minimally invasive surgery; laser interstitial thermal therapy; laser ablation; radiofrequency thermocoagulation; radiotherapy; endoscopy